Review of Nitrous Oxide (N2O) Emissions from Motor Vehicles - Hoekman, S. Kent (SAE International journal of fuels and lubricants, 2020)
Nitrous oxide (N2O) is both an ozone depleting gas and a potent greenhouse gas (GHG), having a global warming potential (GWP) value nearly 300 times that of carbon dioxide (CO2). While long known to be a trace by-product of combustion, N2O was not considered a pollutant of concern until the introduction of the three-way catalyst (TWC) on light-duty gasoline vehicles in the 1980s. These precious metal-containing catalysts were found to increase N2O emissions substantially. Through extensive research efforts, the effects of catalyst type, temperature, air/fuel ratio, space velocity, and other factors upon N2O emissions became better understood. Although not well documented, N2O emissions from non-catalyst vehicles probably averaged 5-10 mg/mi (on the standard FTP test), while early generation TWC-equipped vehicles exceeded 100 mg/mi. As emissions control systems evolved to meet increasingly stringent criteria pollutant standards, N2O emissions also decreased. Today’s Tier 3 vehicles are required to meet a U.S. Environmental Protection Agency (EPA) N2O tailpipe standard of 10 mg/mi. N2O emissions from diesel engines and vehicles became of concern in the 2000s, when catalytic control devices such as diesel particulate filters (DPFs), lean oxides of nitrogen (NOx) traps (LNTs), and selective catalytic reduction (SCR) units were introduced to control PM and NOx. As with gasoline vehicles, N2O emissions from diesel applications are a balance between N2O formation and destruction within these catalytic devices. Modern U.S. light-duty diesel vehicles must comply with the same 10 mg/mi N2O standard that applies to gasoline vehicles; modern heavy-duty diesel (HDD) engines must comply with EPA’s recently established N2O standard of 100 mg/bhp-hr. The total GWP of motor vehicle exhaust is dominated by CO2 emissions, with N2O contributing only 1-2%. Furthermore, the total mass of N2O emissions from mobile sources is declining - largely due to turnover of the light-duty fleet. Consequently, N2O emissions from motor vehicles do not represent a significant contribution to global GHGs.